EFFECTIVE STRATEGIES FOR TEACHING VOCABULARY TO YOUNG LEARNERS - HENDRA EKA PUTRA (Ta'dib, 2011)
Vocabulary learning is very necessary and an indispensable part of any language learning process. In the ESL context, vocabulary not only supports the four language skills; listening, speaking, reading, and writing, but also mediates between ESL students and content-area classes in that the students often find that lack of vocabulary knowledge is an obstacle to learning. This article focuses on and discusses effective strategies for teaching vocabulary to young learners which greatly assist English language learners in their journey of language acquisition and also expedite the language learning processKata kunci: effective strategies, vocabulary, young learners